Proceedings of the First Workshop on Online Social Networks 2008
DOI: 10.1145/1397735.1397737
|View full text |Cite
|
Sign up to set email alerts
|

Do social networks improve e-commerce?

Abstract: Social networks have made a significant impact on how today's Internet users communicate, search for and share data. Numerous proposals have been made to improve existing distributed systems by leveraging the inherent trust built into social links. Many believe that augmenting online marketplaces with social networking should improve trust between transaction partners and improve user satisfaction. In this paper, we perform a detailed study of Overstock Auctions, a novel auction site that integrates social lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(54 citation statements)
references
References 21 publications
0
51
0
3
Order By: Relevance
“…Conventional computermediated communicative tools, such as e-mail or text-based chat, are regarded as having lower social presence and social context cues when compared to face-to-face communication. However, different authors have suggested that it is possible to manipulate the technological experience to enhance social presence and thereby improve different mediated activities 56 such as online learning, 57 e-commerce, 58 and healthcare. 59 Riva and colleagues 60 recently suggested that a subject is present within a virtual group if he is able to put his own intentions (presence) into practice and to understand the intentions of the other group members (social presence).…”
Section: Flowmentioning
confidence: 99%
“…Conventional computermediated communicative tools, such as e-mail or text-based chat, are regarded as having lower social presence and social context cues when compared to face-to-face communication. However, different authors have suggested that it is possible to manipulate the technological experience to enhance social presence and thereby improve different mediated activities 56 such as online learning, 57 e-commerce, 58 and healthcare. 59 Riva and colleagues 60 recently suggested that a subject is present within a virtual group if he is able to put his own intentions (presence) into practice and to understand the intentions of the other group members (social presence).…”
Section: Flowmentioning
confidence: 99%
“…When two persons are not directly connected, the trust between them can be modeled by their distance (the number of hops between them). In particular, a real world study [17] finds that people tend to trust others if they are connected through some trust relationship; however, the number of hops between them must be small. Thus, given a trust radius, which constrains how far away can a trusted person be, the likelihood that the distance between one person to another is within this radius can be used to evaluate the trust between those non-adjacent pairs.…”
Section: Figure 1: Running Examplementioning
confidence: 99%
“…The benefits of online social networks have gone beyond connecting people with information, as many recent studies have exploited online social networks for a variety of important applications, including mitigating multiple identities attacks (also known as Sybil attacks) [27], improving online marketplaces [28], and spreading positive influence [29].…”
Section: Related Workmentioning
confidence: 99%